The timing of our tooth growth is an evolutionary relic. Issue 3 (July 2014) - Dean, Christopher; Cole, Tim
<x xml:space="preserve">Abstract</x> Our teeth grow quickly, then slowly, then speed up again. But the rate of growth has not kept pace with our evolutionary history. Christopher Dean and Tim Cole find a fascinating link that sheds light on how humans diverged from apes.